South Sulawesi Milkfish (Chanos Chanos) Scale Waste as a New Anti-inflammatory Material in Socket Preservation - Djais, Arni Irawaty; Mappangara, Surijana; Gani, Asdar; Achmad, Harun; Endang, Sherly; Tjokro, Jennifer; Raja, Nurhadijah (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: One of South Sulawesi’s huge brackish water fishery product is milkfish (Chanos chanos). Scales are wasted in milkfish processing. However, they are a good source of chitosan, which has been found to promote anti-inflammation, wound healing, and bone regeneration. AIM: This study aims to determine the effect of milkfish scales waste on the inflammatory response of wound healing after tooth extraction by tumor necrosis factor-alpha (TNF-α) and interleukin (IL)-6 analysis. METHODS: This is a post-test-only control group design study. Thirty-two Cavia cobaya were divided into four groups: (1) Socket preservation using milkfish scales chitosan, (2) milkfish scales chitosan + bovine xenograft, (3) bovine xenograft as a positive control, and (4) placebo as a negative control, then were sacrificed on 3rd, 7th, 14th, and 28th days. The mandible jaw specimen was taken for immunohistochemical analysis to determine the levels of TNF-α and IL-6. The data were analyzed using the Kolmogorov–Smirnov test, Levene’s test, and one-way analysis of variance. RESULTS: On days 3, 7, 14, and 28, groups with chitosan added showed lower levels of TNF-α and a faster decrease in IL-6 expressions compared to those without chitosan. CONCLUSION: Milkfish scale chitosan suppresses TNF-α and IL-6 production, thus reducing inflammation in socket preservation.